2010
DOI: 10.1016/j.heares.2010.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the electrode–neuron interface of cochlear implants: Effects of neural survival, electrode placement, and the partial tripolar configuration

Abstract: The partial tripolar electrode configuration is a relatively novel stimulation strategies that can generate more spatially focused electric fields than the commonly used monopolar configuration. Focused stimulation strategies should improve spectral resolution in cochlear implant users, but may also be more sensitive to local irregularities in the electrode-neuron interface. In this study, we develop a practical computer model of cochlear implant stimulation that can simulate neural activation in a simplified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
111
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(124 citation statements)
references
References 44 publications
10
111
0
3
Order By: Relevance
“…This was similar to the results of Berenstein et al (2010), who also found a significantly reduced EFI width as long as the σ of pTP stimulation was greater than 0.5. Although modeling studies (Bonham and Litvak 2008;Goldwyn et al 2010) suggest that larger σ for pTP stimulation may lead to more focused or narrower distributions of electrical potentials, there was insufficient power to perform the correlation test between the width of the EFI pattern and σ across the small number of subjects in this study. Steered pTP Stimuli.…”
Section: Efi Patternsmentioning
confidence: 93%
“…This was similar to the results of Berenstein et al (2010), who also found a significantly reduced EFI width as long as the σ of pTP stimulation was greater than 0.5. Although modeling studies (Bonham and Litvak 2008;Goldwyn et al 2010) suggest that larger σ for pTP stimulation may lead to more focused or narrower distributions of electrical potentials, there was insufficient power to perform the correlation test between the width of the EFI pattern and σ across the small number of subjects in this study. Steered pTP Stimuli.…”
Section: Efi Patternsmentioning
confidence: 93%
“…For example, compared to standard pTP mode, apically shifted pTP mode is expected to elicit lower pitch percepts with increasing α 1.3 mm for all electrodes. These parameters were adapted from Goldwyn et al (2010). Real CI users would have variable neural survival (Nadol et al 2001) and electrode-neuron distances (Finley and Skinner 2008), but that information was not available and thus was not modeled for the subjects in this study.…”
Section: Computational Modelmentioning
confidence: 99%
“…Table 1 summarizes the various stimulation configurations achievable with steered pTP mode using different combinations of α and σ. A computational model that simulates intra-cochlear potential fields and auditory neural response to CI stimulation (Goldwyn et al 2010) was used to investigate loudness and pitch perception with steered pTP mode. Similar models have been used to study loudness growth with standard pTP stimulation (Litvak et al 2007) and simulate current focusing and steering in various modes (Bonham and Litvak 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations